2020
DOI: 10.2147/lctt.s186843
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Current Understanding Of Asbestos-Induced Epigenetic Changes Associated With Lung Cancer</p>

Abstract: Asbestos is a naturally occurring mineral consisting of extremely fine fibres that can become trapped in the lungs after inhalation. Occupational and environmental exposures to asbestos are linked to development of lung cancer and malignant mesothelioma, a cancer of the lining surrounding the lung. This review discusses the factors that are making asbestos-induced lung cancer a continuing problem, including the extensive historic use of asbestos and decades long latency between exposure and disease development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 114 publications
0
19
0
Order By: Relevance
“…Asbestos was widely used in building, textiles and insulation materials until the late 1900s, and exposures have been described both in occupational and non-occupational settings, with often a long latency period (30 years or more) between exposure and development of cancer [22]. While the occupational risk of lung cancer from asbestos has been described with higher frequency in men, one meta-analysis found that women were at slightly higher risk compared to men of developing lung cancer from a non-occupational exposure to asbestos [23]. There is a paucity of cohort studies evaluating the risk of non-occupational asbestos exposure with the development of lung cancer; thus the severity of this risk, particularly in women, may be underrepresented currently.…”
Section: Asbestosmentioning
confidence: 99%
“…Asbestos was widely used in building, textiles and insulation materials until the late 1900s, and exposures have been described both in occupational and non-occupational settings, with often a long latency period (30 years or more) between exposure and development of cancer [22]. While the occupational risk of lung cancer from asbestos has been described with higher frequency in men, one meta-analysis found that women were at slightly higher risk compared to men of developing lung cancer from a non-occupational exposure to asbestos [23]. There is a paucity of cohort studies evaluating the risk of non-occupational asbestos exposure with the development of lung cancer; thus the severity of this risk, particularly in women, may be underrepresented currently.…”
Section: Asbestosmentioning
confidence: 99%
“…A link between the hypermethylation of promotor DNA and inflammation has been shown in many forms of cancer, including asbestos-related lung cancer [ 133 , 134 ]. Molecular genetic analysis have shown changes in the number of DNA copies, changes in the profiles of many microRNAs, and dysregulation of the expression of certain genes in asbestos-associated lung cancer [ 130 , 133 , 134 ]. However, how asbestos fibers directly or indirectly affect cells in lung cancer and how they interact with cells at the molecular level is currently not known [ 17 ].…”
Section: Asbestos and Micrornamentioning
confidence: 99%
“…Although DNA damage-inducible genes, such as TP53 and GADD153, are up-regulated in asbestos treated cells ( Johnson and Jaramillo, 1997 ), accumulation of fibres in the lung and the continuous production of ROS/RNS causes repeated DNA damage, leading to increased genetic instability, a hallmark of neoplastic development ( Nymark et al, 2008 ). Although the mechanism by which asbestos induces epigenetic changes is not fully understood, several studies have shown that both phagocytosis of fibres by AM and oxido-reduction reactions on fibre surfaces are known to generate ROS that result in DNA damage and oxidative stress, leading to genetic alterations ( Cheng et al, 2020 ). High iron content of amphibole asbestos explains how iron-induced Fenton reactions also contribute to increased ROS ( Cheng et al, 2020 ) and it was observed that iron-rich amphibole asbestos species induce phosphorylated histone γ-H2AX ( Msiska et al, 2010 ) marker of epigenetic alteration and gene-specific DNA methylation ( Mossman, 2017 , Öner et al, 2018 , Mossman and Gualtieri, 2020 ).…”
Section: The Fpti Model Linked To the Key Characteristics Of Carcinogensmentioning
confidence: 99%